A new compact micro-ball lens structure at the cleaved tip of microfiber coupler for displacement sensing - Jasim, A.A.; Zulkifli, Ahmad Zarif; Muhammad, M.Z.; Harun, Sulaiman Wadi; Ahmad, Harith (Elsevier, 2013)
A compact micro-ball lens structure is fabricated at the cleaved tip of microfiber coupler (MFC) waist for displacement sensor application. The MFC is made by fusing and tapering two optical fibers using a flame brushing technique. It is then cleaved at the center of the minimum waist region. Then a micro-ball lens is formed at the tip of the microfiber by an arcing technique using a fusion splicing machine. The proposed displacement sensor uses the micro-ball lens as a probe and a reflector as a target. As the target is moved from the micro-ball lens, an interference fringe is obtained due to the interference between two reflected beams from the micro-ball lens and the reflector. At the smallest displacement of 0.6 mm, the output spectrum shows the interference fringes with highest extinction ratio and largest free spectral range (FSR). Both extinction ratio and FSR reduces following the power trend line with correlation coefficient of 0.99 as the displacement increases. The Q resonant factor of the comb spectrum increases from 1628 to 38,286 as the displacement increases from 0.6 to 3.6 mm.